Meeting between members of the Cabinet and representatives of the Trades Union Congress Industrial Committee on the coal situation (verbatim report) : (1926/11/08) - Trades Union Congress. General Council. Special Industrial Committee ; Baldwin, Stanley Baldwin, Earl, 1867-1947
8 November 1926